Notes on two lyrics by Lina Kostenko - Wright, John (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2022)
Many of the lyrics of Lina Kostenko are so immediately engaging that a reader may fail to notice their great complexity and internal structure. In the present article, the author analyzes two such lyrics in some detail, using techniques that might be called structuralist. The analyses, however, begin with no pre-selected methodological framework, but simply start where the lyrics themselves seem to suggest and follow that thread of thought, examining various aspects of the poems. The interpretations built on these analyses are significantly richer than a superficial reading would allow, and therefore, the results may be of interest not only to scholars of Ukrainian poetry, but to the general reader, as well. In the first lyric examined, two lines that are almost lexically identical lead to an examination of a complex mirror-structure that reveals a picture of a continuum between the extremes of metaphor and metonym. A morphological peculiarity of the poem then reveals that it is a response and rebuke to a lyric by the Russian poet Fyodor Tyutchev. With attention paid to the poem’s intricate structure and to the work to which it is a response, the analysis reveals that Kostenko’s lyric may have an anti-imperial meaning that was invisible to the authorities at the time of its publication. In the analysis of the second lyrics, the author begins with a large and memorable rhyme-set, examination of which leads to observations that reveal the unusual self-similar structure of the poem. Further analysis reveals the poem to be a work of verbal art that functions on multiple levels of organization at the same time. After the two analyses, the author makes broader remarks about his general impression of Kostenko’s extremely masterful work, a brief suggestion about introducing this work to anglophone students of Ukrainian literature, and a suggestion for future work on Kostenko’s poetry.